2008
DOI: 10.1097/rli.0b013e31815f3172
|View full text |Cite
|
Sign up to set email alerts
|

The ACTIVE Trial: Comparison of the Effects on Renal Function of Iomeprol-400 and Iodixanol-320 in Patients With Chronic Kidney Disease Undergoing Abdominal Computed Tomography

Abstract: The incidence of CIN was significantly higher after IV administration of iodixanol-320 than iomeprol-400. The mean rise in SCr from baseline was also higher in patients receiving iodixanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 34 publications
2
83
0
Order By: Relevance
“…The results of the present study are in agreement with the most results obtained by others reports Kato et al and Mehran et al [19][20][21][22][23][24][25][26][27]. In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The results of the present study are in agreement with the most results obtained by others reports Kato et al and Mehran et al [19][20][21][22][23][24][25][26][27]. In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-).…”
Section: Discussionsupporting
confidence: 83%
“…In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-). This result is consistent with Wang et al, Liu et al and Nozue et al founded serum level of cystatin C is a reliable marker for CIN at 24 hours p<0.001 and serum creatinine increased significantly at 48 hours, also study carried by Wacker-Gussmann et al [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] found that cystatin C level and the cystatin C/creatinine ratio independently predict the risk of CIN in patients undergoing coronary angiography, but another study by Ribichini et al [32] found a significant increase in serum cystatin C concentrations 12 hours earlier than serum creatinine, therefore a rise of serum cystatin C at 12 hours from baseline was the earliest predictor of CIN than serum creatinine [18].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In a review of 7 prospective observational studies, the overall incidence of CIN was 5.4 % in patients with CKD who intravenously received low-or iso-osmolar contrast media, which suggested that intravenous administration of contrast media may pose a smaller risk of CIN as compared with that seen with intraarterial administration [42]. Table 7 lists the incidence of CIN in patients with CKD after receiving different contrast media [5,[65][66][67][68][69][70]. Table 8 Recently, CAG and catheter-based revascularization have become common procedures, and the use of contrast media has increased substantially.…”
Section: Level Of Evidence: Iva Grade Of Recommendation: Not Applicablementioning
confidence: 99%